Psychometric validation of the spanish translation of the original Problematic internet use questionnaire in young undergraduate students at a private university in Metropolitan Lima - Otiura Trisano, Solange (2022)
The aim of this study was to adapt the Problematic Internet Use Questionnaire (PIUQ) for university students in Lima. The original English version (Demetrovics et al., 2008) was translated into Spanish and tested in 247 students from a private university in the Lima metropolitan area. The internal consistency of the scale was assessed with Cronbach’s alpha and McDonald’s omega coefficients. The original three-factor structure (obsession, neglect, and control disorder) was examined through confirmatory factor analysis (CFA). The alpha coefficient for the total scale was .88; the obsession subscale obtained .80, neglect, .67, and control disorder, .82. In turn, the omega coefficients were .89, .80, .68 y .83, respectively. CFA revealed the best fit index was the three-factor model after three items from neglect were removed. In sum, the Spanish version of the PIUQ shows adequate internal consistency for the total scale, as well as for the obsession and control disorder subscales. However, the neglect subscale needs to be further revised.